Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/vaccines9050469
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards COVID-19 Vaccination among Hospital Staff—Understanding What Matters to Hesitant People

Abstract: Hospital staff are a priority target group in the European COVID-19 vaccination strategy. Measuring the extent of COVID-19 vaccination hesitancy and understanding the reasons behind it are essential to be able to tailor effective communication campaigns. Using the Health Belief Model (HBM) as a theoretical framework, a survey was conducted among staff members of a Belgian three-site hospital center between 6 and 20 January 2021. Multivariable logistic ordinal regression was performed to assess determinants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
46
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 27 publications
9
46
1
2
Order By: Relevance
“…However, at 77%, the willingness to receive a COVID-19 vaccination was also high among individuals who had not been inoculated against influenza. Our data confirm the observation by Spinewine and colleagues that individuals who receive influenza vaccines also show positive attitudes toward COVID-19 vaccines [ 22 ]. Using the 5C theoretical model to determine psychological antecedents for vaccination, Kwok et al showed that influenza vaccination was associated with stronger vaccination confidence, collective responsibility, and weaker risk perception (complacency), perceived barriers (constraints), and benefit-risk trade-offs (calculation).…”
Section: Discussionsupporting
confidence: 91%
“…However, at 77%, the willingness to receive a COVID-19 vaccination was also high among individuals who had not been inoculated against influenza. Our data confirm the observation by Spinewine and colleagues that individuals who receive influenza vaccines also show positive attitudes toward COVID-19 vaccines [ 22 ]. Using the 5C theoretical model to determine psychological antecedents for vaccination, Kwok et al showed that influenza vaccination was associated with stronger vaccination confidence, collective responsibility, and weaker risk perception (complacency), perceived barriers (constraints), and benefit-risk trade-offs (calculation).…”
Section: Discussionsupporting
confidence: 91%
“…An important and recurring pattern seen in different studies is the higher prevalence of COVID-19 vaccine hesitancy among nurses [ 3 , 61 ]. The higher level of COVID-19 vaccine acceptance among physicians and dentists, compared to other HCWs, was reported previously (e.g., in Poland) and should be addressed with proper interventional measures including improving the trust levels in safety and efficacy of COVID-19 vaccines among nurses, who are considered among the highest risk groups for infection risk [ 3 , 57 ].…”
Section: Discussionmentioning
confidence: 97%
“…A recent study from Germany among emergency medical services personnel reported a lower acceptance rate of 57.0%, with males and participants of a higher educational level showing a higher propensity to vaccinate, which is in line with our findings [ 56 ]. A lower COVID-19 vaccine acceptance rate was also reported among Belgian hospital staff (58.0%) [ 57 ]. A much lower COVID-19 vaccine acceptance rate, of merely 21.0%, was reported among Egyptian HCWs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Spinewine et al acknowledged potential side effects (60.9%), and the impression that the vaccine was developed too quickly (45.1%). Other reasons included the impression that the vaccine may not be effective against mutants, and the fact that respondents did not consider themselves at risk of serious complications from COVID-19 [ 64 ]. It should be stressed that, even though available SARS-CoV-2/COVID-19 vaccines represent the “end-stage” of a pipeline that began several years ago [ 65 ], as they were developed and delivered in less than a year, in emergency settings, concerns about their actual safety and effectiveness have been repeatedly associated with moderate acceptance, hesitancy, or reluctance [ 66 , 67 ], including in HCWs [ 47 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such results were not unexpected, having been consistently reported by most available studies [ 25 , 26 , 44 , 47 ]. For example, Spinewine et al [ 64 ] identified that the most important reasons why hesitant respondents would get vaccinated include the protection of loved ones and family (84.1%), colleagues (62.1%), or patients (60.1%), to get back to normal life (63.7%), to collectively get out of the crisis (60.6%), or to protect themselves (40.8%).…”
Section: Discussionmentioning
confidence: 99%